Passing through a prairie country : a novel - Staples, Dennis E. (Counterpoint, 2025)
"For decades, a dark force has terrorized the Languille Lake reservation. Only spoken of in whispers as "the sandman," he lurks in the Hidden Atlantis Lake Resort and Casino, the reservation's main attraction and source of revenue, leeching its patrons' dreams and ambitions and also preventing the ghosts that linger there from moving on. Fleeing a breakup, Marion Lafournier, a mid-twenties Ojibwe, seeks solace in the slot machine's siren song. Here he falls afoul of the sandman, an encounter Marion barely escapes through the timely intervention of his cousins Alana and Cherie, who both work at the casino and are intimately aware of the sandman's power. Meanwhile, Glenn Nielan, only recently out of the closet and an aspiring documentarian, hopes to capture the faces of the Ojibwe land while experiencing the casino's thrills. But he will learn that all who choose to play the sandman's games are in danger of falling into his grasp"--